Effects of salicylic acid on fresh weight change, chlorophyll and protein amounts of radish (Raphanus sativus L.) seedlings - Çanakçi, Songül (My University, 2008)
This study examined the effects of various concentrations (0, 0.2, 1 and 2 mM) of salicylic acid on fresh weight change, pigment and protein amounts of ten-day-old radish (Raphanus sativus L. cv. White) seedlings grown under controlled conditions. The solutions were applied to the roots of one-week-old seedlings for 3 days through an enclosed system. According to the results, it was found that 0.2 mM SA did not affect fresh weight gain, pigment and protein amounts of the seedlings, that 1 and 2 mM SA administration prevented fresh weight gain and additionally, that these two concentrations significantly reduced chlorophyll (a+b) and protein amounts of the seedlings. It was concluded that high concentrations of salicylic acid produced osmotic and toxic stress in radish seedlings, thereby preventing fresh weight gain and reducing pigment and protein amounts. © 2008 Asian Network for Scientific Information.
Keywords: Chlorophyll; Fresh weight; Protein; Radish; Salicylic acid